Designing an Interactive Educational Game for Class IV Students of Cahaya Azhari Primary School - Gunawan, Syahrizal Ilham; Purwawijaya, Ellanda; Rambe, Aripin (Journal of Technology and Computer, 2026)
One of the main problems in mathematics learning at the elementary level, especially in fourth grade, is the low learning motivation of students. Game-based learning using interactive media is believed to enhance students’ engagement and understanding through appealing visuals and enjoyable game mechanics. This study aims to design and develop an interactive educational game based on GameMaker Studio 2 as a mathematics learning medium for fourth-grade students at SD Cahaya Azhari, aligned with the learning outcomes of the Merdeka Curriculum. The research employed the Research and Development (R&D) method with stages including needs analysis, design, development, implementation, and evaluation. Research instruments consisted of expert validation, student and teacher response questionnaires, and pretest–posttest assessments. Validation results showed an excellent category (material 94.5%, media 96.2%). Student and teacher responses reached 92.8% and 94.1%, respectively. Effectiveness testing indicated an improvement in learning outcomes with an N-Gain value of 0.78 (high category). Thus, the developed educational game is declared feasible and effective as an engaging and interactive mathematics learning medium for fourth-grade students.